Parasitosis intestinales en poblaciones Mbyá-Guaraní de la Provincia de Misiones, Argentina: Aspectos epidemiológicos y nutricionales - Navone, Graciela Teresa (2006)
Intestinal parasite infestation in indigenous Mbyá-Guaraní communities in Misiones, Argentina, was described and associated with nutritional status and environmental and cultural factors. The results were compared with those from Takuapí, a neighboring indigenous population, and the nearest urban population, Aristóbulo del Valle. The Ritchie,Willis, and Kato Katz techniques were used to analyze the stool samples. Anthropometric parameters were analyzed and earth samples processed. From a total sample of 296 individuals analyzed in the four populations, 100 (87.7%), 63 (88.7%), 49 (96.1%), and 50 (82%) were infested in Kaaguy Poty, Yvy Pytá, Takuapí, and Aristóbulo del Valle, respectively. 84% of infested individuals had multiple parasites. The 43% of the individuals presented malnutrition, and 87% of these were infested. There was an association between use of latrines and Giardia lamblia (p < 0.01); open-air defecation, lack of footwear, and hookworms (p < 0.01); and housing type and total helminthes (p < 0.01). Earth samples were contaminated with parasites. The results suggest the relationship between environmental contamination and high prevalence of intestinal parasites in these human populations.